The Griffiths Development Scales‐Chinese (GDS‐C): A cross‐cultural comparison of developmental trajectories between Chinese and British children. (1st February 2018) - Tso, W. W. Y.; Wong, V. C. N.; Xia, X.; Faragher, B.; Li, M.; Xu, X.; Ao, L.; Zhang, X.; Jiao, F.‐Y.; Du, K.; Shang, X.; Wong, P. T. Y.; et al.
Abstract: Background: The Griffiths Mental Development Scales (GMDS) are used in many countries to assess the development of children from birth to 8 years. There is a need for accurate and culturally appropriate developmental assessment tools for Chinese children. Here, we adapted the GMDS for use in Chinese children and compare the developmental trajectories between Chinese and British children. Methods: Children with typical development were recruited from 7 urban cities in China between 2009 and 2013. The Griffiths Mental Development Scales‐Chinese (GDS‐C) were adapted and used to assess the development of urban Chinese children. Developmental curves were computed for 6 subscales using learning management system methods and compare against the British curves from the Griffiths Mental Development Scales‐Extended Revised (GMDS‐ER). Results: The GDS‐C were used to assess the developmental status of 815 Chinese children. Plots of the 1st, 5th, 10th, 25th, 50th, 75th, 90th, 95th, and 99th percentiles, and full percentile tables were obtained, which showed similar trends to data from the British GMDS‐ER. Conclusions: The Chinese developmental curves obtained from the GDS‐C showed similarities and differences to the developmental curves from the British GMDS‐ER. The development of urban Chinese children should be assessed with the culturally appropriate GDS‐C.